Valorization of Polyethylene Terephthalate to Muconic Acid by Engineering Pseudomonas Putida - Liu, Pan; Zheng, Yi; Yuan, Yingbo; Zhang, Tong; Li, Qingbin; Liang, Quanfeng; Su, Tianyuan; Qi, Qingsheng (International journal of molecular sciences, 2022)
Plastic waste is rapidly accumulating in the environment and becoming a huge global challenge. Many studies have highlighted the role of microbial metabolic engineering for the valorization of polyethylene terephthalate (PET) waste. In this study, we proposed a new conceptual scheme for upcycling of PET. We constructed a multifunctional Pseudomonas putida KT2440 to simultaneously secrete PET hydrolase LCC, a leaf-branch compost cutinase, and synthesize muconic acid (MA) using the PET hydrolysate. The final product MA and extracellular LCC can be separated from the supernatant of the culture by ultrafiltration, and the latter was used for the next round of PET hydrolysis. A total of 0.50 g MA was produced from 1 g PET in each cycle of the whole biological processes, reaching 68% of the theoretical conversion. This new conceptual scheme for the valorization of PET waste should have advantages over existing PET upcycling schemes and provides new ideas for the utilization of other macromolecular resources that are difficult to decompose, such as lignin.